DESAIN KOMUNIKASI DALAM UPAYA MENYELESAIKAN KONFLIK ANTAR AKTOR PADA KASUS PULAU REMPANG - Octavyanida, Ni’matus Gesa; Putri, Tiara Cahaya; Fathurrahman, Reza (Jurnal Ilmiah Publika, 2023)
This study discusses the role of the government in providing public services and infrastructure development to increase economic growth and community productivity. The case study focuses on the development of Rempang Eco City in Indonesia, which faced challenges due to the lack of involvement of the local community and the reliance on technical aspects only. The relocation efforts did not consider the social and emotional aspects of the community, leading to conflicts and human rights violations. It highlights the need for an effective communication strategy involving multi-actors to ensure that development projects are sustainable and do not discriminate against local indigenous populations. The government, indigenous communities, and BP Batam need to understand each other's interests and concerns to minimize the emergence of sectoral egos, dominance, and asymmetric information.  The research study used a qualitative approach with descriptive methods to explore the conflict between sectors on Rempang Island. Data collection was conducted through document study, gathering information from various credible secondary sources. The data analysis was descriptive, aiming to provide an interpretation of the conflicts and their implications. The theoretical basis of the text is the importance of effective communication in policy formulation and implementation, which is crucial for the proper functioning of democracy in a developing country like Indonesia.